PENGARUH KEPEMIMPINAN DAN KOMITMEN ORGANISASI TERHADAP TURNOVER INTENTION - Rudy Prabowo (Wahana Islamika: Jurnal Studi Keislaman, 2018)
Turnover intention from members of the organization can be detrimental to the organization, including in the ranks of Gunungkidul Police Criminal Investigation. Such losses, such as when there are senior human resources in the field of Criminal Investigation have the desire to move, it will be difficult to get a replacement, so maintaining the old HR is more important than recruiting new ones. Since maintaining human resources in the field of investigation is very important, research is needed on the causes of organizational members having the desire to leave the organization or turnover intention. The population of this research is 148 from Gunungkidul Police Criminal Investigation. The sampling technique is saturated sampling, which takes all of the total population. Data analysts use regression analysis with the help of SPSS 21. The results of the study prove that there is a significant negative influence between leadership variables and organizational commitment with turnover intention. So the better the leadership in Gunungkidul Police Criminal Investigation and the high commitment to the organization can reduce turnover intention